2014
DOI: 10.1177/0734282914521978
|View full text |Cite
|
Sign up to set email alerts
|

Test Anxiety and College Students With Attention Deficit Hyperactivity Disorder

Abstract: Test anxiety was examined in college students with and without attention deficit hyperactivity disorder (ADHD). Results indicated that, relative to college students without ADHD, college students with ADHD reported higher total test anxiety as well as specific aspects of test anxiety, including worry (i.e., cognitive aspects of test anxiety) and emotionality (i.e., physiological aspects of test anxiety). Effect sizes were large for total test anxiety and the worry aspect of test anxiety. Nearly half of college… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 34 publications
4
18
0
Order By: Relevance
“…This may have inflated group differences where they existed. This would be particularly relevant for test anxiety, although our results are highly consistent with Nelson et al (), who found that college students with ADHD who did not have comorbid anxiety and/or depression also reported much higher test anxiety than college students without ADHD. Finally, the study required students with ADHD to make time estimations, rate their behaviors, and compare themselves to others.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This may have inflated group differences where they existed. This would be particularly relevant for test anxiety, although our results are highly consistent with Nelson et al (), who found that college students with ADHD who did not have comorbid anxiety and/or depression also reported much higher test anxiety than college students without ADHD. Finally, the study required students with ADHD to make time estimations, rate their behaviors, and compare themselves to others.…”
Section: Discussionsupporting
confidence: 92%
“…ADHD participants were significantly more likely to feel unprepared for tests and exams, believe they do not study enough to get the grades they would like, and perceive their preparation for tests and exams to be worse than controls. Additionally, consistent with previous research (Nelson et al, ), students with ADHD reported significantly higher test anxiety, and these effect sizes were large. These findings were notable given that students with ADHD reported similar class attendance and study time, environments, and planning as students without ADHD.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Although specific rates of anxiety disorders in college students have not been determined, it is clear that many students with ADHD also struggle with anxiety symptoms and disorders. For example, Nelson, Lindstrom and Foels [23] reported that close to half of college students with ADHD reported clinically meaningful levels of test anxiety. Similarly, those with ADHD also experience higher rates of depression than the general college student population [24][25][26].…”
Section: Attention Deficit Hyperactivity Disorder and Success In Collegementioning
confidence: 99%
“…Elevated levels of test anxiety are also linked to procrastination and loss of motivation to engage in academic work (Mavilidi, Hoogerheide, & Paas, 2014). Although levels of test anxiety depend on the social and educational functions of both the schools and tests involved (Song, Bong, Lee, & Kim, 2015;Varela & Hensley-Maloney, 2009), for example whether the tests are low-or high-stakes (Segool, Carlson, Goforth, von der Embse, & Barterian, 2013), it typically weakenes educational performance, and burdens individuals regardless of the cultural setting when levels are excessive (Liew et al, 2014;Nelson et al, 2014). Nonetheless, in Sweden test anxiety has drawn little attention from the educational field (see Nyroos et al, 2015).…”
Section: Test Anxietymentioning
confidence: 99%